Discriminative Validity and Reliability of the Single-Leg Squat and Single-Leg Landing Frontal Plane Kinematics in Individuals with Lower Limb Functional Deficits - Jean Marlon Machado; Marcelo Peduzzi de Castro; Amandda de Souza; Carlos Alberto Atherinos Pierri; Francisco Xavier de Araujo; Heiliane de Brito Fontana; Caroline Ruschel (Biomechanics)
Background/Objectives: Kinematic measurements obtained from functional tests have been used to identify associated and risk factors for the development of lower limb dysfunction, allowing targeted interventions to reduce potential risks and guide rehabilitation. It is necessary to identify variables and tests with adequate reliability and with the capability to discriminate individuals with and without lower limb functional deficits. This study aimed to determine which single-legged test (single-leg squat and single-leg landing) and variables (angle at deepest instant and range of motion) present the best reliability and capability to discriminate individuals with and without lower limb functional deficits. Methods: The frontal plane kinematics of 86 adults, divided into 2 groups (43 with lower limb functional deficits and 43 without), as classified by the Lower Extremity Functional Scale, were assessed during single-leg squat and single-leg landing tasks. The differences between groups in trunk, pelvis, hip, and knee ranges of motion and angles were tested using the independent T test or Mann–Whitney U test, and the test–retest, inter-rater, and intra-rater absolute (standard error of measurement and minimal detectable difference) and relative (intraclass correlation coefficient) reliability were calculated. Results: Trunk (r = 0.47), hip (r = 0.40), and knee (r = 0.35) angles at the deepest instant, as well as range of motion of the trunk (r = 0.33), pelvis (r = 0.47), and knee (r = 0.32) during the single-leg landing discriminated between groups (p < 0.05). For the single-leg squat, no variable discriminated the groups. Test–retest, inter-rater, and intra-rater reliability ranged from poor to excellent, with minimal detectable differences remaining below 19°. Conclusions: The single-leg landing and pelvis range of motion were the most effective tests and variables for discriminating individuals with and without lower limb functional deficits. Most variables demonstrated moderate test–retest and excellent inter-rater and intra-rater reliability.